(untitled) (Swiss Medical Weekly, 2015)
Local vascular injury is detectable with optical coherence tomography (OCT) after catheter-based renal denervation (RDN). However, it is unclear whether the number and type of vascular lesions or the number of ablation points could affect blood pressure (BP) reduction. The aim of the study was to assess the impact of vascular injury induced by RDN detected with OCT and the number of ablation points on BP response after 1, 3 and 6 months. METHODS: RDN was either performed with a Simplicity® catheter or an EnligHTNTM multielectrode basket followed by OCT. BP was recorded prospectively as office measurement and 24-hour ambulatory blood pressure monitoring (24-h ABPM) at each time point. Correlations between type and number of vascular lesions, as well as ablation points, on BP reduction were performed. RESULTS: Out of 16 patients, two were lost to BP follow-up. We documented a BP reduction at 1, 3 and 6 months in both office and 24-h ABPM. The Δmean office systolic BP (SBP) reduction was –18.75 ± 24.55 mm Hg, –20.58 ± 16.92 mm Hg and –18.75 ± 29.39 mm Hg, respectively, and the Δmean 24h-ABPM SBP reduction was –6.50 ± 23.45 mm Hg, –16.88 ± 26.64 mm Hg and –13.89 ± 21.20 mm Hg, respectively. The number of vascular lesions did not correlate with office and 24h-SBP and diastolic BP reduction. However, there was a correlation between ablation points and office Δmean SBP reduction at 6 months (p <0.02). CONCLUSIONS: Our study demonstrates for the first time that the number and type of vascular lesions as assessed with OCT did not predict the success of BP reduction after RDN. However, we observed a substantial decrease in office SBP in relation to the number of ablation points at 6 months.